Barke poljske kraljiceThe Boats of the Polish Queen - Nartnik, Vlado (Studia mythologica Slavica, 2012)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The short ballad titled Mlada Vida in zamorec v barki (Young Vida and a Negro in a Boat) is but a part of a longer ballad with the title Lepa Vida (Fair Vida) that contains further description of Vida’s stay at the Spanish court, which is reminiscent of the legend Deveti mož (Ninth Man). Of particular interest is the three-week boat ride that in the legend corresponds to three boats that may be explained with three moon phases. The romance Poljska kraljica (Polish Queen) starts with the multiplied counting of boats. The romance no longer focuses on the celestial voyage of the pretty Vida from Taurus to Scorpio and to Pegasus but from Pegasus in the west to Leo and to Virgo in the east. Between them, precisely in the south and located between Taurus and Gemini, are the key moon phases above the constellation of Orion, given that the new moon above this constellation once denoted the vernal equinox. The lunar year thus commenced after the spring new moon with the initial first quarter moon in Virgo, and ended with the twelfth first quarter moon in Leo. Since the counting of first quarter moons resembles to the counting of books in Homer’s poems The Iliad and The Odyssey, as well as in Vergil’s The Aeneid, this opens up the question of the similarity between the siege of Troy in The Iliad and the siege of Venice in Poljska kraljica.